The Influence of Digital Literacy, Learning Access and Participation on Marketing Employee Competence through the Utilization of Integrated Learning Systems at PT. Bank XXXX Regional Office XXX - Fransiska, R. Meutia; Lumbanraja, Prihatin; Absah, Yeni (Indonesian Journal of Advanced Research, 2025)
Digital transformation in banking is crucial for enhancing employee competencies, especially in marketing roles, amid rapid technological changes. However, challenges such as limited digital literacy, restricted access to learning platforms, and low participation in online training hinder employees' ability to meet the demands of the digital banking sector. This study explores how digital literacy, learning access, and participation affect marketing staff competencies at PT. Bank XXXX, with integrated learning systems utilization. Using a quantitative approach, data from surveys, interviews, and documents are analyzed. The research conducted from October 2024 to June 2025, show that improving digital literacy, access to learning resources, and participation positively impact competencies, with integrated learning systems strengthening these effects, supporting the bank’s digital transformation.